2008
DOI: 10.1519/jsc.0b013e3181660605
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Whole-Body Vibration on the Hoffmann Reflex

Abstract: The extent to which motoneuron pool excitability, as measured by the Hoffmann reflex (H-reflex), is affected by an acute bout of whole-body vibration (WBV) was recorded in 19 college-aged subjects (8 male and 11 female; mean age 19 +/- 1 years) after tibial nerve stimulation. H/M recruitment curves were mapped for the soleus muscle by increasing stimulus intensity in 0.2- to 1.0-volt increments with 10-second rest intervals between stimuli, until the maximal M-wave and H-reflex were obtained. After determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 20 publications
7
67
2
2
Order By: Relevance
“…T he use of whole body vibration (WBV) as an exercise modality is relevant to sports scientists and strength and conditioning coaches due to the array of physiological and performance measurements which it affects (2)(3)(4)(5). In particular, acute exposure to WBV has been shown to result in increased respiration (19,20) and energy expenditure (9), increased cutaneous blood flow (19), increased anabolic hormone response (12), and increased activation of the tonic vibration reflex (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T he use of whole body vibration (WBV) as an exercise modality is relevant to sports scientists and strength and conditioning coaches due to the array of physiological and performance measurements which it affects (2)(3)(4)(5). In particular, acute exposure to WBV has been shown to result in increased respiration (19,20) and energy expenditure (9), increased cutaneous blood flow (19), increased anabolic hormone response (12), and increased activation of the tonic vibration reflex (16).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, acute exposure to WBV has been shown to result in increased respiration (19,20) and energy expenditure (9), increased cutaneous blood flow (19), increased anabolic hormone response (12), and increased activation of the tonic vibration reflex (16). However, the use of an acute bout of WBV as a method to potentiate athletic performance measures remains unclear (3,6,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This greater muscle activation could be due to an augmented excitatory input from the muscle spindle. 8 However, researchers 27,28 have demonstrated that reflex activity either remains unchanged or decreases after a bout of whole-body vibration. Although spinal reflex excitability decreased, the changes in homosynaptic depression (presynaptic mechanism that regulates the function of the Ia afferent-motoneuron synapse) point to a particular mechanism that may directly improve neuromuscular function after whole-body vibration.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is highly variable and may be associated with individual differences other than sex, training specificity, or conditioning. 28 Postural sway in the M/L direction is considered a better predictor of the risk of falling than A/P sway, even for individuals who have no recent history of falling. 29 Our results showed a greater sway decrease in the M/L than A/P direction (approximately 50% versus 25%) after SAV training.…”
Section: Discussionmentioning
confidence: 99%